Anti-aging polyethylene plastic and preparation method thereof

By using 5-amino-2-mercaptobenzimidazole and selenium dioxide coordinated in polyethylene plastics to form a cross-linked structure, the problems of flammable and poor aging properties of polymer materials are solved, and the efficient anti-aging and flame retardant effects of polyethylene plastics are achieved.

CN119505398AActive Publication Date: 2025-02-25HUAIAN RUIYIKE POLYMER TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411545819.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-25
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Existing polymer materials are flammable and have poor aging properties, which pose safety hazards and reduce their use value.

Method used

Anti-aging agents are prepared by the coordination combination of 5-amino-2-mercaptobenzimidazole with selenium dioxide, and the introduction of selenium atoms to capture free radicals, and combined with 3-aminopropyl trihydroxysilane to form a crosslinked structure, improving the anti-aging and flame retardant properties of polyethylene plastics.

Benefits of technology

It significantly improves the mechanical strength, thermal stability and flame retardant properties of polyethylene plastics, delays the aging process, and enhances the safety and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113747530000071
    Figure BDA0005113747530000071
Patent Text Reader

Abstract

The invention discloses an anti-aging polyethylene plastic and a preparation method thereof, and relates to the technical field of plastic preparation. The anti-aging agent is prepared through coordination binding of 5-amino-2-mercaptobenzimidazole and selenium dioxide, selenium atoms are introduced, chain reaction is prevented, plastic aging is slowed down, and meanwhile sulfur inhibits pyrolytic reaction and slows down flame propagation speed; then, the mixture participates in dehydration condensation reaction in modified polyethylene to jointly form a cross-linked structure, so that the mechanical strength and the thermal stability of the plastic are remarkably improved. Wherein the modified polyethylene is subjected to double-bond polymerization reaction with 1, 3-butadiene and 1, 5-hexadienol, so that the connection stability is improved, and the strength of the plastic is improved; the strength and toughness of the plastic are remarkably improved, the heat resistance is improved, the plastic can adapt to various environments, abrasion is reduced, the silicon element is heated to form a glassy film or carbon black to cover the surface of the plastic during combustion, heat and oxygen are isolated from entering, and the flame-retardant effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic preparation, in particular to an anti-aging polyethylene plastic and a preparation method thereof. Background Art

[0002] With the development of society and the advancement of science and technology, various polymer materials have been prepared to meet people's needs. Polymers are widely used in many fields such as aerospace, industrial packaging, and military because of their easy processing, cheap raw materials, excellent strength and toughness, and good corrosion resistance. From large automotive parts to small food packaging, polymers can be found. Although the application of polymers has brought great convenience to production and life, there are also some potential safety issues. Since most polymers are mainly composed of carbon, hydrogen, and oxygen elements, polymers composed of these elements are extremely flammable. Once ignited, they will burn rapidly, generating toxic gases and a large amount of heat. At the same time, the molten droplets produced when the polymer burns will also cause the combustion of other combustibles, causing immeasurable harm.

[0003] At the same time, during the processing, storage and use of polymer materials, due to the influence of environmental factors, their physical, chemical and mechanical properties undergo irreversible changes and eventually lose their use value. This phenomenon is called aging. The aging of polymer materials is often divided into internal aging and external aging. Internal aging phenomena mainly include internal stress relaxation, post-crystallization, phase separation of multiphase materials, migration of accelerators, etc., which are mainly caused by the thermodynamic instability of polymer materials; external aging phenomena mainly include stress cracking, fatigue cracking, thermal oxidation degradation, expansion, etc. of materials, which are caused by the physical and chemical interactions of the environment in which the polymer materials are located. Therefore, it is particularly important to invent a flame retardant and anti-aging polymer material. Summary of the invention

[0004] The object of the present invention is to provide an anti-aging polyethylene plastic and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing anti-aging polyethylene plastic, comprising the following preparation steps:

[0006] (1) Dissolve 4 to 8 parts of 5-amino-2-mercaptobenzimidazole in 150 to 350 parts of ethanol, stir at 800 rpm for 20 to 40 minutes, dropwise add 2 to 4 parts of selenium dioxide ethanol solution, heat to 50° C., react for 1 to 2 hours, filter out the solid, wash with ethanol three times, and dry at 60 to 70° C. for 5 to 9 hours to obtain an anti-aging agent;

[0007] (2) Under an inert gas atmosphere, 5 to 9 parts of triisobutylaluminum are added to 12 to 18 parts of 1,5-hexadienol, stirred at 60 rpm for 0.5 to 1.5 hours, 68 to 122 parts of toluene are added, the rotation speed is adjusted to 100 rpm, 1,3-butadiene gas is introduced until the pressure is 2 MPa, 2 to 4 parts of catalyst are added, the temperature is raised to 60 to 70° C., and the reaction is carried out for 4 to 8 hours. During the reaction, 1,3-butadiene gas is continuously introduced to keep the pressure constant. After the reaction is completed, air is connected, 24 to 36 parts of hydrochloric acid ethanol solution are added, stirred for 40 to 60 minutes, the solid is filtered out, washed with acetone three times, and dried at 70 to 90° C. for 6 to 10 hours to obtain a composite polyolefin;

[0008] (3) 7 to 13 parts of the composite polyolefin and 63 to 117 parts of toluene are stirred at 100° C. and 60 rpm for 20 to 40 minutes, 2 to 4 parts of 3-aminopropyltrihydroxysilane, 1 to 3 parts of an anti-aging agent, and 0.5 to 1.5 parts of 7-methylhexacyclic bicyclic guanidine are added, and stirring is continued for 40 to 60 minutes, and then the temperature is lowered to 60 to 70° C., and the reaction is carried out for 5 to 9 hours to obtain a reaction solution, which is subjected to precipitation treatment and dried at 70 to 90° C. for 4 to 8 hours to obtain a modified polyolefin;

[0009] (4) 42 to 58 parts of high-density polyethylene, 25 to 39 parts of modified polyolefin, 0.2 to 0.8 parts of lubricant, and 1 to 3 parts of filler are mixed uniformly, and extruded into granules after mixing. The head temperature is 170 to 180°C, the screw speed is 160 to 240 r / min, the extrusion pressure is 6 to 12 MPa, and the shear rate is 150 to 250 s -1 , to obtain anti-aging polyethylene plastic.

[0010] Furthermore, the dripping rate in step (1) is 2 drops / s.

[0011] Furthermore, the concentration of selenium dioxide in the selenium dioxide ethanol solution in step (1) is 0.5 mol / L.

[0012] Furthermore, the inert gas in step (2) is any one of nitrogen, argon and helium.

[0013] Furthermore, the catalyst in step (2) is a mixture of one or more of a chromium-based catalyst, a titanium-based catalyst, and a vanadium-based catalyst.

[0014] Furthermore, the concentration of hydrochloric acid in the hydrochloric acid ethanol solution in step (2) is 2 mol / L.

[0015] Furthermore, the precipitation process in step (3) is as follows: add 6 parts of ethanol to 1 part of the reaction solution, stir at 1000 rpm for 30 to 50 minutes, filter out the solid, and wash it with ethanol three times.

[0016] Furthermore, the model of the high-density polyethylene in step (4) is any one of HDPE5000S, HDPE5301AA, and HDPE5070.

[0017] Furthermore, the lubricant in step (4) is a mixture of one or more of EBS, erucamide, oleamide, and zinc stearate.

[0018] Furthermore, the filler in step (4) is a mixture of one or more of talc, cellulose, calcium carbonate and kaolin.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The invention prepares an anti-aging agent by coordination and combination of the mercapto group of 5-amino-2-mercaptobenzimidazole and selenium dioxide, introduces selenium atoms with strong reducing property, captures and removes free radicals, prevents chain reaction from occurring, thereby slowing down plastic aging and preliminarily achieving anti-aging effect; at the same time, hydrogen ions in the imidazole ring can react and combine with free radicals to stabilize plastic molecules and prevent oxidative decomposition, thereby enhancing anti-aging performance; on this basis, the presence of sulfur element can inhibit pyrolysis reaction and prevent premature decomposition of materials, and combine with oxygen element during combustion to slow down flame propagation speed, thereby achieving flame retardant performance; finally, the amino group in the anti-aging agent is utilized to participate in the dehydration condensation reaction in the modified polyolefin to jointly form a cross-linked structure, thereby significantly improving the mechanical strength and thermal stability of the plastic.

[0021] Among them, the modified polyolefin forms a network structure through the double bond polymerization reaction between 1,3-butadiene and 1,5-hexadienol protected by triisobutylaluminum, thereby improving the shear resistance, thereby increasing the stability of the connection and preliminarily improving the strength of the plastic; then the triisobutylaluminum protection is removed under acidic conditions to expose the hydroxyl groups, which are then dehydrated and condensed with the hydroxyl groups in 3-aminopropyltrihydroxysilane to form a three-dimensional network structure, which significantly improves the strength and toughness of the plastic. The presence of cross-linking points creates a heat-resistant structure between the molecular chains, thereby improving the heat resistance. At the same time, the formed silicon-oxygen bonds have a large bond energy, which enhances the interaction force between the plastic molecules and the surface hardness. It can adapt to various environments such as high temperature, ultraviolet rays, and oxidation, prevent molecular cracking, and thus maintain the thermal and chemical stability of the plastic, reduce wear, and achieve anti-aging effects. On this basis, during combustion, the silicon element is heated to form a glass-like film or carbon black covering the plastic surface, isolating heat and oxygen from entering, and achieving a flame retardant effect. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the anti-aging polyethylene plastics prepared in the following examples are as follows:

[0024] Tensile strength and elongation at break before aging: Films of the same size as those of the embodiment and the comparative example were prepared and tested according to GB / T1040.3.

[0025] Tensile strength and elongation at break after aging: Films of the same size as those of the embodiment and the comparative example were made and aged using a xenon lamp according to GB / T16422.2. After aging for 3000 h, the films were taken out and tested for tensile strength and elongation at break according to GB / T 1040.3.

[0026] Oxygen index: films of the same size prepared from the embodiment and the comparative example were tested according to GB / T 2406.

[0027] Example 1: (1) 4 parts of 5-amino-2-mercaptobenzimidazole were dissolved in 150 parts of ethanol, stirred at 800 rpm for 20 min, 2 parts of selenium dioxide ethanol solution with a selenium dioxide concentration of 0.5 mol / L were added dropwise at a rate of 2 drops / s, the temperature was raised to 50°C, reacted for 1 hour, the solid was filtered out, washed with ethanol 3 times, and dried at 60°C for 5 hours to obtain an antioxidant;

[0028] (2) Under an argon atmosphere, 5 parts of triisobutylaluminum were added to 12 parts of 1,5-hexadienol, stirred at 60 rpm for 0.5 h, 68 parts of toluene were added, the rotation speed was adjusted to 100 rpm, 1,3-butadiene gas was introduced until the pressure was 2 MPa, 2 parts of chromium catalyst were added, the temperature was raised to 60°C, and the reaction was carried out for 4 h. During the reaction, 1,3-butadiene gas was continuously introduced to keep the pressure constant. After the reaction was completed, the air was connected, 24 parts of ethanolic hydrochloric acid solution with a hydrochloric acid concentration of 2 mol / L was added, and the mixture was stirred for 40 min. The solid was filtered out, washed with acetone 3 times, and dried at 70°C for 6 h to obtain a composite polyolefin;

[0029] (3) 7 parts of composite polyolefin and 63 parts of toluene were stirred at 100° C. and 60 rpm for 20 min, 2 parts of 3-aminopropyltrihydroxysilane, 1 part of anti-aging agent, and 0.5 parts of 7-methylhexacyclic bicyclic guanidine were added, and stirring continued for 40 min. Then, the temperature was lowered to 60° C. and reacted for 5 h to obtain a reaction solution. 1 part of the reaction solution was added to 6 parts of ethanol, and stirred at 1000 rpm for 30 min. The solid was filtered out, washed with ethanol 3 times, and dried at 70° C. for 4 h to obtain a modified polyolefin.

[0030] (4) 42 parts of HDPE5000S, 25 parts of modified polyolefin, 0.2 parts of erucic acid amide and 1 part of talc were mixed evenly, and extruded into granules after mixing. The head temperature was 170°C, the screw speed was 160r / min, the extrusion pressure was 6MPa, and the shear rate was 150s -1 , to obtain anti-aging polyethylene plastic.

[0031] Example 2: (1) 6 parts of 5-amino-2-mercaptobenzimidazole were dissolved in 250 parts of ethanol, stirred at 800 rpm for 30 min, 3 parts of selenium dioxide ethanol solution with a selenium dioxide concentration of 0.5 mol / L was added dropwise at a rate of 2 drops / s, the temperature was raised to 50°C, the reaction was carried out for 1.5 hours, the solid was filtered out, washed with ethanol 3 times, and dried at 65°C for 7 hours to obtain an antioxidant;

[0032] (2) Under nitrogen atmosphere, 7 parts of triisobutylaluminum were added to 15 parts of 1,5-hexadienol, stirred at 60 rpm for 1.0 h, 95 parts of toluene were added, the rotation speed was adjusted to 100 rpm, 1,3-butadiene gas was introduced until the pressure was 2 MPa, 3 parts of titanium catalyst were added, the temperature was raised to 65°C, and the reaction was carried out for 6 h. During the reaction, 1,3-butadiene gas was continuously introduced to keep the pressure constant. After the reaction was completed, the air was connected, 30 parts of 2 mol / L hydrochloric acid ethanol solution was added, and the mixture was stirred for 50 min. The solid was filtered out, washed with acetone 3 times, and dried at 80°C for 8 h to obtain a composite polyolefin;

[0033] (3) 10 parts of composite polyolefin and 90 parts of toluene were stirred at 100° C. and 60 rpm for 30 min, 3 parts of 3-aminopropyltrihydroxysilane, 2 parts of anti-aging agent, and 1.0 part of 7-methylhexacyclic bicyclic guanidine were added, and stirring continued for 50 min. Then the temperature was lowered to 65° C. and reacted for 7 h to obtain a reaction solution. 1 part of the reaction solution was added with 6 parts of ethanol, and stirred at 1000 rpm for 40 min. The solid was filtered out, washed with ethanol 3 times, and dried at 80° C. for 6 h to obtain a modified polyolefin.

[0034] (4) 50 parts of HDPE5301AA, 32 parts of modified polyolefin, 0.5 parts of oleic acid amide and 2 parts of cellulose were mixed evenly, and extruded into granules after mixing. The head temperature was 175°C, the screw speed was 200 r / min, the extrusion pressure was 8 MPa, and the shear rate was 200 s-1 , to obtain anti-aging polyethylene plastic.

[0035] Example 3: (1) 8 parts of 5-amino-2-mercaptobenzimidazole were dissolved in 350 parts of ethanol, stirred at 800 rpm for 40 min, 4 parts of selenium dioxide ethanol solution with a selenium dioxide concentration of 0.5 mol / L was added dropwise at a rate of 2 drops / s, the temperature was raised to 50°C, reacted for 2 h, the solid was filtered out, washed with ethanol 3 times, and dried at 70°C for 9 h to obtain an antioxidant;

[0036] (2) In a helium atmosphere, 9 parts of triisobutylaluminum were added to 18 parts of 1,5-hexadienol, stirred at 60 rpm for 1.5 h, 122 parts of toluene were added, the rotation speed was adjusted to 100 rpm, 1,3-butadiene gas was introduced until the pressure was 2 MPa, 4 parts of vanadium catalyst were added, the temperature was raised to 70°C, and the reaction was carried out for 8 h. During the reaction, 1,3-butadiene gas was continuously introduced to keep the pressure constant. After the reaction was completed, the air was connected, 36 parts of 2 mol / L hydrochloric acid ethanol solution was added, stirred for 60 min, the solid was filtered out, washed with acetone 3 times, and dried at 90°C for 10 h to obtain a composite polyolefin;

[0037] (3) 13 parts of composite polyolefin and 117 parts of toluene were stirred at 100° C. and 60 rpm for 40 min, 4 parts of 3-aminopropyl trihydroxysilane, 3 parts of anti-aging agent, and 0.15 parts of 7-methyl hexacyclic bicyclic guanidine were added, and stirring continued for 60 min, then the temperature was lowered to 70° C. and reacted for 9 h to obtain a reaction solution, 1 part of the reaction solution was added to 6 parts of ethanol, and stirred at 1000 rpm for 50 min, the solid was filtered out, washed with ethanol 3 times, and dried at 90° C. for 8 h to obtain a modified polyolefin;

[0038] (4) 58 parts of HDPE5070, 39 parts of modified polyolefin, 0.8 parts of zinc stearate and 3 parts of kaolin were mixed evenly, and extruded into granules after mixing. The head temperature was 180°C, the screw speed was 240 r / min, the extrusion pressure was 12 MPa, and the shear rate was 250 s -1 , to obtain anti-aging polyethylene plastic.

[0039] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (3) is changed to: 10 parts of composite polyolefin and 90 parts of toluene are stirred at 100° C. and 60 rpm for 30 min, 3 parts of 3-aminopropyl trihydroxysilane, 2 parts of selenium dioxide, and 1.0 part of 7-methyl hexacyclic bicyclic guanidine are added, and stirring is continued for 50 min, then the temperature is lowered to 65° C. and reacted for 7 h to obtain a reaction solution, 1 part of the reaction solution is added to 6 parts of ethanol, stirred at 1000 rpm for 40 min, solids are filtered out, washed with ethanol 3 times, and dried at 80° C. for 6 h to obtain a modified polyolefin. The remaining steps are the same as in Example 2.

[0040] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (3) is changed to: 10 parts of composite polyolefin and 90 parts of toluene are stirred at 100° C. and 60 rpm for 30 min, 3 parts of 3-aminopropyl trihydroxysilane, 2 parts of 5-amino-2-mercaptobenzimidazole, and 1.0 part of 7-methyl hexacyclic bicyclic guanidine are added, and stirring is continued for 50 min, then the temperature is lowered to 65° C. and reacted for 7 h to obtain a reaction solution, 1 part of the reaction solution is added to 6 parts of ethanol, stirred at 1000 rpm for 40 min, solids are filtered out, washed with ethanol 3 times, and dried at 80° C. for 6 h to obtain a modified polyolefin. The remaining steps are the same as Example 2.

[0041] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: Under a nitrogen atmosphere, 1,3-butadiene gas is introduced into 95 parts of toluene until the pressure is 2 MPa, the rotation speed is adjusted to 100 rpm, 3 parts of titanium catalyst are added, the temperature is raised to 65°C, and the reaction is carried out for 6 hours. During the reaction, 1,3-butadiene gas is continuously introduced to maintain the pressure unchanged. After the reaction is completed, the air is connected, 10 parts of hydrochloric acid ethanol solution with a hydrochloric acid concentration of 2 mol / L is added, and the mixture is stirred for 50 minutes. The solid is filtered and washed with acetone. The reaction mixture was washed 3 times and dried at 80°C for 8h to obtain a polyolefin; step (3) was changed to: 10 parts of polyolefin and 90 parts of toluene were stirred at 100°C and 60rpm for 30min, 3 parts of 3-aminopropyltrihydroxysilane, 2 parts of anti-aging agent and 1.0 part of 7-methylhexacyclic bicyclic guanidine were added, and the stirring was continued for 50min, and then the temperature was lowered to 65°C and reacted for 7h to obtain a reaction solution, 1 part of the reaction solution was added with 6 parts of ethanol, and stirred at 1000rpm for 40min, and the solid was filtered out, washed with ethanol 3 times, and dried at 80°C for 6h to obtain a modified polyolefin. The remaining steps were the same as those in Example 2.

[0042] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: 10 parts of composite polyolefin and 90 parts of toluene are stirred at 100°C and 60rpm for 30min, 2 parts of anti-aging agent and 1.0 part of 7-methyl hexacyclic bicyclic guanidine are added, stirring is continued for 50min, then the temperature is lowered to 65°C, reacted for 7h, and a reaction liquid is obtained. 1 part of the reaction liquid is added with 6 parts of ethanol, stirred at 1000rpm for 40min, solids are filtered out, washed with ethanol 3 times, and dried at 80°C for 6h to obtain modified polyolefin. The remaining steps are the same as those in Example 2.

[0043] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: 10 parts of composite polyolefin and 90 parts of toluene are stirred at 100°C and 60rpm for 30min, 3 parts of 3-aminopropyltrihydroxysilane and 1.0 part of 7-methylhexacyclic bicyclic guanidine are added, and stirring is continued for 50min, then the temperature is lowered to 65°C, and the reaction is carried out for 7h to obtain a reaction solution. 1 part of the reaction solution is added with 6 parts of ethanol, stirred at 1000rpm for 40min, the solid is filtered out, washed with ethanol 3 times, and dried at 80°C for 6h to obtain a modified polyolefin; step (4) is changed to: 50 parts of HDPE5301AA, 32 parts of modified polyolefin, 2 parts of antioxidant, 0.5 parts of oleic acid amide, and 2 parts of cellulose are mixed uniformly, and the mixture is extruded and granulated. The head temperature is 175°C, the screw speed is 200r / min, the extrusion pressure is 8MPa, and the shear rate is 200s -1 The remaining steps are the same as those in Example 2.

[0044] Effect example

[0045] Table 1 below shows the performance analysis results of the anti-aging polyethylene plastics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0046] Table 1

[0047]

[0048] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that the hydrogen ions in the imidazole ring can react and combine with free radicals to stabilize the plastic molecules and prevent oxidative decomposition, thereby enhancing the anti-aging performance. At the same time, the presence of sulfur can inhibit the pyrolysis reaction and prevent the material from decomposing prematurely. It combines with oxygen during combustion to slow down the flame propagation speed, thereby achieving flame retardant performance. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that selenium atoms have strong reducing properties and can remove free radicals to prevent the occurrence of chain reactions, thereby slowing down the aging of plastics. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that the olefins are grafted by the hydroxyl groups in hexadienol to form a network structure, which can improve the shear resistance, enhance the stability of the connection, and improve the strength of the plastic. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that 3- Aminopropyltrihydroxysilane has multiple active sites, which can dehydrate and condense with the grafted hydroxyl groups in the plastic to form a three-dimensional structure, significantly improving the strength and toughness of the plastic. The presence of cross-linking points produces a heat-resistant structure between the molecular chains, thereby improving the heat resistance. At the same time, the silicon-oxygen bonds formed have a large bond energy, which enhances the interaction force between plastic molecules and the surface hardness. It can adapt to various environments such as high temperature, ultraviolet rays, and oxidation, prevent molecular cracking, and thus maintain the thermal stability and chemical stability of the plastic, reduce wear, and achieve anti-aging effects. During combustion, the silicon element is heated to form a glass-like film or carbon black covering the plastic surface, isolating heat and oxygen from entering, and achieving a flame retardant effect. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that when the anti-aging agent is added to the dehydration condensation process of the modified polyolefin, they can be combined together to form a cross-linked structure to improve the mechanical properties of the plastic.

[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing anti-aging polyethylene plastic, characterized in that: The method comprises the following preparation steps: (1) Dissolve 4 to 8 parts of 5-amino-2-mercaptobenzimidazole in 150 to 350 parts of ethanol, stir at 800 rpm for 20 to 40 minutes, dropwise add 2 to 4 parts of selenium dioxide ethanol solution, heat to 50° C., react for 1 to 2 hours, filter out the solid, wash with ethanol three times, and dry at 60 to 70° C. for 5 to 9 hours to obtain an anti-aging agent; (2) Under an inert gas atmosphere, 5 to 9 parts of triisobutylaluminum are added to 12 to 18 parts of 1,5-hexadienol, stirred at 60 rpm for 0.5 to 1.5 hours, 68 to 122 parts of toluene are added, the rotation speed is adjusted to 100 rpm, 1,3-butadiene gas is introduced until the pressure is 2 MPa, 2 to 4 parts of catalyst are added, the temperature is raised to 60 to 70° C., and the reaction is carried out for 4 to 8 hours. During the reaction, 1,3-butadiene gas is continuously introduced to keep the pressure constant. After the reaction is completed, air is connected, 24 to 36 parts of hydrochloric acid ethanol solution are added, stirred for 40 to 60 minutes, the solid is filtered out, washed with acetone three times, and dried at 70 to 90° C. for 6 to 10 hours to obtain a composite polyolefin; (3) 7 to 13 parts of the composite polyolefin and 63 to 117 parts of toluene are stirred at 100° C. and 60 rpm for 20 to 40 minutes, 2 to 4 parts of 3-aminopropyltrihydroxysilane, 1 to 3 parts of an anti-aging agent, and 0.5 to 1.5 parts of 7-methylhexacyclic bicyclic guanidine are added, and stirring is continued for 40 to 60 minutes, and then the temperature is lowered to 60 to 70° C., and the reaction is carried out for 5 to 9 hours to obtain a reaction solution, which is subjected to precipitation treatment and dried at 70 to 90° C. for 4 to 8 hours to obtain a modified polyolefin; (4) 42 to 58 parts of high-density polyethylene, 25 to 39 parts of modified polyolefin, 0.2 to 0.8 parts of lubricant, and 1 to 3 parts of filler are mixed uniformly, and extruded into granules after mixing. The head temperature is 170 to 180°C, the screw speed is 160 to 240 r / min, the extrusion pressure is 6 to 12 MPa, and the shear rate is 150 to 250 s -1 , to obtain anti-aging polyethylene plastic.

2. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The drop acceleration rate in step (1) is 2 drops / s.

3. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The concentration of selenium dioxide in the selenium dioxide ethanol solution in step (1) is 0.5 mol / L.

4. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The inert gas in step (2) is any one of nitrogen, argon and helium.

5. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The catalyst in step (2) is a mixture of one or more of a chromium-based catalyst, a titanium-based catalyst, and a vanadium-based catalyst.

6. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The concentration of hydrochloric acid in the hydrochloric acid ethanol solution in step (2) is 2 mol / L.

7. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The precipitation process in step (3) is as follows: add 6 parts of ethanol to 1 part of the reaction solution, stir at 1000 rpm for 30 to 50 minutes, filter out the solid, and wash it with ethanol three times.

8. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The model of the high-density polyethylene in step (4) is any one of HDPE5000S, HDPE5301AA, and HDPE5070.

9. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The lubricant in step (4) is a mixture of one or more of EBS, erucamide, oleamide and zinc stearate.

10. The method for preparing an anti-aging polyethylene plastic according to claim 1, characterized in that: The filler in step (4) is a mixture of one or more of talc, cellulose, calcium carbonate and kaolin.

Citation Information

Patent Citations

  • Steel piece cyanide-free copper plating method adopting applied magnetic field

    CN105780074A

  • High-content and high-elasticity special modifier for asphalt, and preparation method thereof

    CN106700578A

  • Rubber multifunctional auxiliary agent 4-methylpiperidinyl dithiocarbamic acid mercaptobenzimidazole selenium, and preparation method and application of rubber multifunctional auxiliary agent 4-methylpiperidinyl dithiocarbamic acid mercaptobenzimidazole selenium

    CN115716819A

  • Aqueous phase pore sealing agent imroving PCB coating oxidation- resistant and corrosion-resistant properties and method for using same

    US20140314967A1

  • Impact-resistant and aging-resistant reflective plastic applied to automobiles

    US20230056991A1